Interleukin-6 rsl800795 polymorphism is not considered as a genetic biomarker in Turkish national skiing running athlete cohort - (:unkn) unknown (Parlar Scientific Publications, 2020)
Athletic performance is considered to be determined by the effect of genetic endowment and environmental factors like nutrition, regular training and psychology. Aim of the present study is to determine the effect of Interleukin-6 (IL-6) rsl800795 polymorphisms in Turkish National Skiing running athletes. A total of 55 individuals, 34 skiers and 21 non-skiers (controls) were enrolled for the study. DNA isolation from buccal samples of athletes was performed by using Invitrogen (Van Allen Way, Carlsbad, CA, USA) commercial kit. Genotyping process was carried out by real-time PCR. GG and GC genotypes were analyzed as equal in athletes. In controls, GG genotype was superior to other genotypes. There was no statistically significant difference in the terms of/L-tf rsl800795 polymorphism between athletes and controls. CC genotype was not detected in both groups. Our results revealed the importance of genetic factors in determining the athlete's sports performance, but there is need for more studies in the terms of IL-6 rsl800795 to clarify their effects on athletic performance. This first report, including the related genetic markers and skiing running athletes will guide scientists for further studies. © 2020 Parlar Scientific Publications. All rights reserved.
Keywords: Athlete; Athletic performance; Polymorhism; Sport genomic